Self-Esteem Challenges of Nursing Students: An Integrative Review - Leila Valizadeh; Vahid Zamanzadeh; Rahim Badri Gargari; Akram Ghahramanian; Faranak Jabbarzadeh Tabrizi; Brian Keogh (Tabriz University of Medical Sciences, 2016)
Introduction: Self-esteem among nursing students is important in providing high-quality serviceto clients, yet each study in this field has described only a portion of existing relevant knowledge.Integrative review studies are the best practice for identification of existing nursing knowledge.The purpose of this study was to determine self-esteem challenges among nursing students. Methods: An integrative review was conducted in this study. The databases ProQuest, Medlineon PubMed, Science Direct, Google Scholar and Iran Medix were used for the review. The articleswere retrieved in three steps, including searching by search terms, reviewing the proceedingsbased on inclusion criteria and final retrieval and assessment of the available full texts. We used alist of keywords, including nursing, self-esteem and challenges and mixed them with "AND" and"OR" as a search strategy. Papers were included and eligible if they were associated with problemsrelated to nursing students' self-esteem. Those studies that focused only on the self-esteem ofregistered nurses or patients were excluded. Search results were limited to the years 1960-2014. Results: Our findings showed three major challenges, including challenges associated withinconsistency in determining the level of students' self-esteem, self-esteem associated challengesin professionalism of students, and the psychosocial challenges pertaining to the consequences oflow self-esteem. Conclusion: The findings suggest there is a need for more qualitative research to explore thefactors that contribute to self-esteem in nursing students with a particular focus on the factorsthat increase or decrease self-esteem. In addition, strategies to maintain and increase self-esteemneed to be designed, implemented and evaluated.